The origins of the Syrian conflict climate change and human security - Daoudy, Marwa (Cambridge, United Kingdom Cambridge University Press, 2020)
"This book puts forward a new framework for evaluating the climate-conflict hypothesis that examines the interactions between environmental, economic, and sociopolitical factors at the roots of the Syrian uprising (2011). The Human-Environmental-Climate Security (HECS) framework adopts a critical environmental security perspective to avoid deterministic thinking and recognize local agency by people and governments. Applying the HECS framework to the Syrian case, the author traces the history of climate, water, and food (in)security in Syria in the context of Ba'athist and liberal policies. Ultimately, the book concludes that while climate change might have contributed to the severity of a drought in the mid- to late 2000s, it was ultimately the Syrian government's poor policy decisions that created a nexus of vulnerability in rural agricultural communities"--Provided by publisher.
Climate change and the Syrian revolution -- The many faces of environmental security -- When geography rules history -- Rules of ideology and policy : from Ba'athism to the liberal age -- Vulnerability and resilience : human-environmental-climate security (HECS) in Syria -- Syria : a (hi)story of vulnerability, resistance, and resilience.
Includes bibliographical references and index.
Keywords: Water security -- Syria; Water-supply -- Political aspects -- Syria; Food security -- Political aspects -- Syria; Climatic changes -- Syria; Human security -- Syria; Syria -- Environmental conditions; Syria -- History -- Civil War, 2011- -- Environmental aspects